2011
DOI: 10.1073/pnas.1101273108
|View full text |Cite|
|
Sign up to set email alerts
|

Itch E3 ubiquitin ligase regulates large tumor suppressor 1 stability

Abstract: The large tumor suppressor 1 (LATS1) is a serine/threonine kinase and tumor suppressor found down-regulated in a broad spectrum of human cancers. LATS1 is a central player of the emerging Hippo-LATS suppressor pathway, which plays important roles in cell proliferation, apoptosis, and stem cell differentiation. Despite the ample data supporting a role for LATS1 in tumor suppression, how LATS1 is regulated at the molecular level remains largely unknown. In this study, we have identified Itch, a HECT class E3 ubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
109
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 113 publications
(114 citation statements)
references
References 32 publications
5
109
0
Order By: Relevance
“…One notable post-translational regulation of LATS1/2 is ubiquitination. A WW domain-containing HECT class E3 ubiquitin ligase, ITCH, ubiquitinates LATS1 and promotes cell growth and survival (Ho et al 2011;Salah et al 2011). Another E3 ubiquitin ligase, CRL4 (DCAF1), which is activated in NF2-deficient tumor cells, inhibits LATS1 and LATS2 by ubiquitination in the nucleus (Li et al 2014b).…”
Section: Spatial Regulation Of Mst and Latsmentioning
confidence: 99%
“…One notable post-translational regulation of LATS1/2 is ubiquitination. A WW domain-containing HECT class E3 ubiquitin ligase, ITCH, ubiquitinates LATS1 and promotes cell growth and survival (Ho et al 2011;Salah et al 2011). Another E3 ubiquitin ligase, CRL4 (DCAF1), which is activated in NF2-deficient tumor cells, inhibits LATS1 and LATS2 by ubiquitination in the nucleus (Li et al 2014b).…”
Section: Spatial Regulation Of Mst and Latsmentioning
confidence: 99%
“…Interestingly, we found that the protein levels of the ubiquitin-ligase ITCH increased almost twofold within 24 hours (Fig 4B). ITCH has been reported to ubiquitinate the tumour suppressor LATS1 leading to its degradation (41,42). In addition to this potential ubiquitin-regulated mechanism of LATS1 downregulation, we detected that A-Raf, a potent inhibitor of MST2 (43,44), was elevated.…”
Section: Hgf Regulates the Hippo-pathwaymentioning
confidence: 99%
“…The immunoprecipitated YAP was subjected to 10% SDS-PAGE and stained with commassie blue. The phosphorylated YAP band was cut and identification of YAP and phosphorylated YAP peptides was performed as described (16).…”
Section: Identification Of Yap Phosphorylation Sites By Mass Spectrommentioning
confidence: 99%